Pengaruh Beban Kerja, Profesionalisme dan Disiplin Kerja Guru terhadap Prestasi Kerja Guru SMK-PP Negeri Saree Kabupaten Aceh Besar - Mahdalena, Mahdalena; Arief Syarifuddin, Evi; Yanna, Sri (Singkite Journal, 2024)
Research was conducted on teachers at Saree-PP State Vocational School, Aceh Besar Regency to determine the influence of each variable of workload, professionalism and teacher work discipline on work performance, as well as the joint influence of workload, professionalism and work discipline on work performance. Using quantitative methods with statistical analysis tools, namely multiple regression. The data collection technique uses a valid questionnaire and has a high level of reliability as an instrument. The research results show that: 1) There is a positive and significant effect of workload on work performance, 2) teacher professionalism has a positive effect on work performance, 3) Work discipline also has a positive effect on teacher work performance. 4) Together workload, professionalism and work discipline contribute 66.4% to teacher work performance.